2001
DOI: 10.1097/00006231-200109000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Studies on white blood cell labelling:99 Tcm-HMPAO preferentially labels granulocytes

Abstract: Mixed leucocytes have been labelled in small volumes of plasma using small aliquots of hexamethylpropylene amine oxime (HMPAO) from vials of Ceretec, which were fractionated after reconstitution and stored frozen under nitrogen. Labelling efficiency was found to be independent of HMPAO concentration >8.8 microg.ml-1 and independent of cell concentration at >8x10(7) ml-1. Results are presented from 145 patients referred for white cell scintigraphy. Labelling efficiency was 78.9+/-9.8%. The labelled mixed leucoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
3
5
0
Order By: Relevance
“…The constant and prolonged release of activity allows the lymphatic drainage of the activity to persist and late lymph node accumulation to occur. The same phenomenon was not observed with labelled lymphocytes, but labelling of these cells is known to be more stable [31]. In our study, significant early bladder activity was observed in the six patients investigated with 99m Tc-HMPAO-labelled DCs.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The constant and prolonged release of activity allows the lymphatic drainage of the activity to persist and late lymph node accumulation to occur. The same phenomenon was not observed with labelled lymphocytes, but labelling of these cells is known to be more stable [31]. In our study, significant early bladder activity was observed in the six patients investigated with 99m Tc-HMPAO-labelled DCs.…”
Section: Discussionsupporting
confidence: 83%
“…With 99m Tc-HMPAO, about 50% of the activity initially linked to DCs was released in the supernatant at the late control. This suggests a progressive release of the initially incorporated activity, a phenomenon not observed in white blood cell labelling [31]. Another group previously observed persistent lymph node activity with DCs that were generated and loaded, labelled with 99m Tc-HMPAO and injected in one leg as in our experiment [18].…”
Section: Discussionsupporting
confidence: 62%
“…are likely to have a greater impact on the results. Our labeling efficiency range (17–72%) was comparable to other studies [22]. When performing absolute quantification of uptake, attenuation correction using hybrid imaging, e.g., SPECT/CT should always be considered.…”
Section: Discussionsupporting
confidence: 83%
“…This cell type is involved in the pathophysiology of many processes variable from ischemiaYreperfusion [13] to adult respiratory distress syndrome (ARDS), rheumatoid arthritis, inflammatory bowel diseases [12] and probably also CRPS I. 99m TcYHMPAO has been demonstrated to show a preference for granulocytes [11]. The PMN capability to inflict damage has been credited to its ability either to release toxic granule components or to generate reactive oxygen metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Leukocytes were isolated and labelled with 200 MBq 99m TechnetiumYHexamethylpropyleneamine oxime ( 99m TcYHMPAO), as described by Peters et al [9] and re-injected in the cubital vein. HMPAO is an efficient leukocyte label, and labels granulocytes with more stability than mononuclear leukocytes [10,11]. After one and 4 h gamma camera images were acquired from both hands using a gamma camera (Orbiter; Siemens Medical Systems, Inc., Hoffman Estate, IL, USA).…”
Section: Methodsmentioning
confidence: 99%